Artificial light simulator for solar panels: design and construction in Peru - Fernández Goicochea, William Fernando (2024)
The objective of this research was to design and construct an artificial light machine that simulates the solar illuminations of the coast, highlands, and jungle of Peru, evaluating its impact on solar panels. The methodology included the construction of the machine at the University of Lima and tests with a module composed of an artificial light source, a solar panel, a measurement module, and an ammeter clamp. Tests were conducted varying the illumination to simulate the conditions of the different regions of Peru. The results obtained were 4,8; 7,2 and 4,0 kWh/m² for the simulations of the coast, highlands, and jungle, respectively. The research concluded that it is feasible to develop a solar lighting source that improves the efficiency of solar panels and allows working under stationary conditions. However, it is necessary to increase the number of tests and improve their precision for a more objective evaluation of their practical utility.